Food for talk: Phototalk and commensality - O'Hara, Kenton; Helmes, John; Sellen, Abigail; Harper, Richard; Bhomer, Martin; Hoven, Elise van den (Human-Computer Interaction (Special Issue on Personal Memories), 2012)
Photographic mementos are important signifiers of our personal memories. Rather than simply passive representations of memories to ‘‘preserve’’ the past, these photos are actively displayed and consumed in the context of everyday behavior and social practices. Within the context of these settings, these mementos are invoked in particular ways to mobilize particular social relations in the present. Taking this perspective, we explore how photo mementos come to be used in the everyday social setting of sharing meal. Rather than a simple concern with nutritional consumption, the shared meal is a social event and important cultural site in the organization of family and social life with culturally specific rhythms, norms, rights, and responsibilities. We present a system — 4 Photos — that situates photo mementos within the social concerns of these settings. The system collates photo mementos from those attending the meal and displays them at the dining table to be interacted with by all. Through a real-world deployment of the system, we explore the social work performed by invoking these personal memory resources in the context of real-world settings of shared eating. We highlight particular features of the system that enable this social work to be achieved.